Adult‐onset neuroblastoma: Report of seven cases with molecular genetic characterization. Issue 4 (2nd December 2019) - Duan, Kai; Dickson, Brendan C.; Marrano, Paula; Thorner, Paul S.; Chung, Catherine T.
Abstract: Whereas neuroblastoma is the most common extracranial solid tumor of childhood, less than 5% of cases occur in adults. Pediatric neuroblastoma shows marked heterogeneity of histology and molecular biology. Information about this tumor in adults is limited, especially regarding molecular biology. We report a series of nine neuroblastoma cases diagnosed in adulthood (18 to 40 years old) with molecular biologic characterization in seven. All tumors were Schwannian stroma‐poor, and mostly poorly differentiated. Tumors expressed neural markers including PHOX2B, NB84, synaptophysin, chromogranin, CD56, neuron‐specific enolase, and PGP9.5. Two out of six cases expressed ALK and one had the F1174 L mutation reported in childhood neuroblastoma. Fluorescent in situ hybridization (FISH) revealed MYCN amplification in 2/7 cases, chromosome 1p deletion in 1/5 cases and 17q gain in 4/4 cases. One in five cases showed loss of ATRX expression by immunohistochemistry and alternate lengthening of telomeres by FISH. Zero out of five cases showed rearrangement of the TERT gene by FISH, but one case showed high level amplification. In conclusion, the morphology and immunophenotype of adult‐onset neuroblastoma are similar to pediatric cases although less differentiated than some childhood tumors. Similarly, molecular genetic alterations in adult‐onset neuroblastoma are not unique to this age group. However, 80% of cases tested showed genetic changes that would promote maintenance of telomeres, which is a molecular marker of high risk cases. This may help explain the poor response in adults to pediatric treatment protocols. Additional studies to characterize the biology of this tumor in the adult age group will facilitate the design of more personalized therapeutic approaches.